2013
DOI: 10.1109/jstqe.2013.2238509
|View full text |Cite
|
Sign up to set email alerts
|

50-Gb/s Direct Modulation of a 1.3-μm InGaAlAs-Based DFB Laser With a Ridge Waveguide Structure

Abstract: We demonstrate 50-Gb/s direct modulation by using 1.3-μm distributed-feedback lasers with a ridge waveguide structure. We employed InGaAlAs material for a multiple-quantum well to obtain a low damping factor K, and fabricated a ridge waveguide structure buried in benzocyclobutene to realize a structure with a low parasitic capacitance. In addition, to obtain high maximum frequency relaxation oscillations fr, we designed the cavity length L), and achieved a 3-dB-down frequency bandwidth of 34 GHz. We realized 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
52
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(53 citation statements)
references
References 15 publications
0
52
0
1
Order By: Relevance
“…However, for datacom applications, it is crucial to reduce the cavity length so that the LDs can be used as directly modulated LDs (DMLs) in order to suppress power consumption and to enhance bandwidth. Indeed, DMLs with cavity lengths less than 200 μm are widely used in this application [15], [16]. In this context, we have to develop multiple quantum well (MQW) lasers on Si because there are difficulties shortening the cavity length of the QD lasers due to their small modal volume.…”
Section: Introductionmentioning
confidence: 99%
“…However, for datacom applications, it is crucial to reduce the cavity length so that the LDs can be used as directly modulated LDs (DMLs) in order to suppress power consumption and to enhance bandwidth. Indeed, DMLs with cavity lengths less than 200 μm are widely used in this application [15], [16]. In this context, we have to develop multiple quantum well (MQW) lasers on Si because there are difficulties shortening the cavity length of the QD lasers due to their small modal volume.…”
Section: Introductionmentioning
confidence: 99%
“…An InGaAlAs multiple-quantum well (MQW) active layer has a large conduction band offset, and an Al-based MQW layer has been introduced into high-speed directly modulated short cavity LDs [1]. However, LD characteristics are degraded when the operating temperature increases at modulation speeds exceeding 50 Gb/s [2]. This is because a larger optical gain within a stricter carrier confinement even at high temperatures is required in order to achieve further high-speed direct modulation within a much shorter cavity for a wide temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…Manuscript Directly modulated lasers can be used as a straight forward microwave photonics source given the simplicity of their principle of operation and their demonstrated high frequency bandwidths. Recent developments have shown that 50 Gb/s directly modulated laser data rates can be achieved [4]. These lasers can operate at a wavelength of 1.3 μm with optical cavities based on distributed feedback resonators.…”
Section: Introductionmentioning
confidence: 99%